2021
DOI: 10.1002/hep.31642
|View full text |Cite
|
Sign up to set email alerts
|

Dual Targeting of G9a and DNA Methyltransferase‐1 for the Treatment of Experimental Cholangiocarcinoma

Abstract: Ayudas para apoyar a grupos de investigación del sistema Universitario Vasco (IT971-16);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 50 publications
4
34
0
1
Order By: Relevance
“…In fact, the expression of DNMT1, which is in charge of the maintenance of the DNA methylation pattern during mitosis, has been reported to be upregulated in hepatic fibrosis and HCC [113,114] . It has also been demonstrated that DNMTs are upregulated in others types of cancer such as gastric cancer [115] , prostate cancer [116] , CCA [117] , and pancreatic cancer [118] . Indeed, DNMT1, DNMT3A, and DNMT3B are known to also be upregulated in HB tumors [18,119] .…”
Section: Dna Methylation In Hepatoblastomamentioning
confidence: 99%
“…In fact, the expression of DNMT1, which is in charge of the maintenance of the DNA methylation pattern during mitosis, has been reported to be upregulated in hepatic fibrosis and HCC [113,114] . It has also been demonstrated that DNMTs are upregulated in others types of cancer such as gastric cancer [115] , prostate cancer [116] , CCA [117] , and pancreatic cancer [118] . Indeed, DNMT1, DNMT3A, and DNMT3B are known to also be upregulated in HB tumors [18,119] .…”
Section: Dna Methylation In Hepatoblastomamentioning
confidence: 99%
“…This sequence of events can be accelerated and enhanced by the chronic administration of the hepatotoxin and carcinogen TAA, which also hastens the emergence of markers of CCA development, as seen above. We recently described that when Jnk ∆hepa mice are treated with a single dose of the carcinogen diethylnitrosamine (DEN), and then chronically challenged with CCl 4 (DEN/CCl 4 model), instead of hepatocellular carcinomas, these animals develop cyst-like structures with molecular features compatible with cholangioma and malignant CCA [ 1 , 17 ], including upregulated expression of NOTCH1, GS and markers of oval cells ( Ck19 , Sox9 , Yap1 mRNA), as well as increased proliferation measured as Pcna mRNA levels ( Supplementary Figure S8A–I ), similar to those observed now in response to TAA. In view of this, and of the recognized risk of CCA development in patients with fibrocystic liver diseases, including CD [ 13 , 31 , 32 ], it was important to provide conclusive evidence of the malignant nature of the lesions developed in these mice.…”
Section: Resultsmentioning
confidence: 99%
“…However, when subjected to the DEN/CCl 4 challenge (as described in Supplementary Figure S8A ), 22-week-old Jnk ∆hepa mice developed strong activation of the UPR ( Figure 9 B) and a potent cystogenic and fibrogenic response ( Figure 9 C). We recently described that the malignant progression of CCA-like lesions in DEN/CCl 4 treated Jnk ∆hepa mice can be inhibited by the administration of CM272, a novel epigenetic drug that simultaneously targets the histone methyltransferase G9a and DNA-methyltransferase 1 (DNMT1) [ 17 ]. Interestingly, CM272 administration, as described in Supplementary Figure S9A , markedly reduced the expression of UPR effectors ( Figure 9 B) and significantly attenuated the fibrogenic and cystogenic responses ( Figure 9 C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CM-272 counteracts the pro-fibrogenic metabolic reprogramming of HSC and inhibits CCl 4 -induced fibrogenesis in vivo [ 136 ]. The efficacy of CM-272 has also been recently demonstrated in cholangiocarcinoma, a type of hepatobiliary tumor for which no effective systemic therapies exist [ 137 ].…”
Section: Harnessing Epigenetic Alterations For Therapymentioning
confidence: 99%